Water and nitrogen conservation enhance summer soybean (Glycine max) yield via improved photosynthesis and pod formation traits - Huangcheng He; Rui Guo; Kaihong Deng; Shuhao Pang; Jianguo Liu (Frontiers in Sustainable Food Systems)
In arid Xinjiang, high crop yields depend on substantial water and nitrogen inputs, but this leads to inefficient resource use. This study investigated whether water and nitrogen inputs could be reduced without compromising yield in post-wheat relay-cropped soybean, aiming for more efficient resource utilization. In 2023 and 2024, a field experiment was conducted at the Experimental Station of the College of Agriculture, Shihezi University. The experiment employed a two-factor split-plot design, with irrigation amount as the primary factor with three levels: W1 (3,360 m3·hm−2, 33.3% reduction from W3), W2 (4,200 m3·hm−2, 16.6% reduction from W3), and W3 (5,040 m3·hm−2, conventional irrigation). Nitrogen application rate (pure nitrogen) was the secondary factor with four levels: N1 (0 kg·hm−2), N2 (105 kg·hm−2, 46.2% reduction from N4), N3 (150 kg·hm−2, 23.1% reduction from N4), and N4 (195 kg·hm−2, conventional application) – totaling 12 treatments. Among all treatments, only the water-saving (W2) and nitrogen-saving (N3) combination (W2N3) achieved agronomic traits, pod formation, and yield components statistically equivalent to conventional practice (W3N4). W2N3 maintained near-equivalent yield to W3N4 (reduction of 0.84–1.32%) while conserving water and N. This reduction lowers environmental risks (e.g., N leaching, salinity) and has the potential to improve soil health through optimized organic matter input. Economically, it reduced production costs by 483.91 CNY·hm−2, increasing net profit by 350.10–408.79 CNY·hm−2. Reducing irrigation by 16.6% and N by 23.1% optimizes resource efficiency, supports agricultural sustainability, and offers viable strategies for arid agroecosystems.